Environmental perspectives : a brief overview of selected topics - Shifrin, Neil (SpringerBriefs in Environmental Science, 2014)
This short, readable book is intended as a big-picture introduction/overview for environmental students and lay-people involved with environmental issues. Every freshman in college intending to study environmental science should read it. It begins with a historical perspective on waste and environmental control. Basic instruction on some important fundamentals faced by environmental professionals every day, such as sampling, analysis, data visualization, risk assessment and forensic chemistry are provided in the following chapter. Important regulatory fundamentals, such as the National Contingency Plan, which is the U.S. regulatory framework for addressing hazardous waste is also defined. The book concludes with pertinent and provocative considerations on the future of environmental management, such as alternative approaches (technical impracticability), the "not-in-my-backyard syndrome," and the safety of chemicals in consumer products. The book contains many useful facts about waste production rates, energy use and recycling rates-all referenced to allow substantiation and provide a springboard for further research.